The Application of “Blended Learning-Rigorous Mathematical Thinking” Model to Improve Students’ Spatial Thinking Ability - Makmun Hidayat; Mustadji Mustadji; Bachtiar Saiful Bachri; Bakhrul Khair Amal (BIRCU, 2021)
This research is a quantitative descriptive study that explains the improvement of students' spatial thinking skills after the implementation of the blended learning-rigorous mathematical thinking model, hereinafter referred to as the BL-RMT model. Spatial thinking ability (KBSp) which is measured in this study is related to the mathematics subject in the aspect of geometry. The design of this study used a